Analysis Of JKN Mobile User Satisfaction Using Servqual Method at Private Hospitals in West Bekasi - Kurniawaty, Deasy Erika; Kusumadi, Lourdes Joanna; Barnavio, Allisa Laurina; Bernarto, Innocentius (Universitas Pelita Harapan, 2025)
As the national health insurance provider for all Indonesians, the Social Security Administering Body (BPJS) is working toward enhancing its service with JKN Mobile. It is anticipated that the JKN Mobile application will enable customers to obtain more user-friendly and effective services. The research uses a quantitative approach. The population in this study is 77. This study uses the purposive sampling method with certain criteria for a total of 65 samples. The instrument uses a questionnaire. Data analysis uses SERVQUAL. Data processing is using IBM SPSS version 25. The results on the collected data show Cronbach’s Alpha value for perception of 0.823 and expectations of 0.782, greater than 0.60, meaning that the questionnaire of this study is reliable. The conclusion of the study conducted in Private Hospitals in West Bekasi shows that the menu and features of JKN Mobile are perceived as incomplete and, to some extent, are not functioning properly most of the time.